Method of noninvasive teeth extraction due to the usage of «Luxator Directa» tools - Ugrin, M.; Got’, S.; Shubenko, T.; Romanko, A. (Actual Dentistry, 2018)
Method of noninvasive teeth extraction due to the usage of «Luxator Directa» tools